INTERNALISASI NILAI NILAI PANCASILA SILA PERTAMA TERHADAP MAHASISWA DI INDONESIA UNTUK TERBENTUKNYA TATA NILAI HARMONIS ANTARA UMAT BERAGAMA - delimatarigan Delima Putri Parda Tarigan (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2024)
This article discusses the importance of internalizing the values of Pancasila, particularly the first principle "Belief in One God," among Indonesian students to create a harmonious value system among different religious communities. Given the high religious diversity in Indonesia, the application of Pancasila values in higher education is crucial for character development among students. This research aims to analyze the methods of internalizing these values and their impact on tolerance within campus environments. The methodology employed is qualitative research with a literature study approach, providing an in-depth understanding of the challenges faced by students in this process. The findings indicate the need for a comprehensive approach to teaching Pancasila to enhance understanding. With strategic initiatives from educational institutions and community involvement, it is hoped that students will develop mutual respect and contribute to a harmonious society.